Особливості організації дизайн-об’єктів інформаційно-комунікативного середовища сучасного міста (на прикладі м. Харків) - Сосницький, Юрій Олександрович (Хмельницький національний університет міського господарства імені О. М. Бекетова, 2019)
У дисертації представлені результати дослідження проектно–художньої організації дизайн-об’єктів інформаційно-комунікативних середовищ. Автором відокремлені практичні світові прийоми задіяння дизайн-об’єктів у простори міст. Види інформаційно-комунікативних середовищ та приводи до їх реорганізації. Виявлені функціональні пріоритети дизайн-об’єктів у міському просторі відносно їх «духовних» та «тілесних» властивостей. Досліджена низка реорганізованих та історичних локацій міста з приводу виявлення позитивних і негативних інформаційно-комунікативних якостей. Аналізується сучасний стан теоретичного надбання у розвитку власного «дизайн-коду» міста. У ході дослідження пропонується ряд інноваційних принципів і прийомів, які зможуть реорганізувати сучасне положення інформаційно-комунікативного простору з урахуванням функціональності кожної окремої локації та власної естетичної ідентифікації. Відокремлюється комплекс інтерактивного і новітнього обладнання, яке повинно знаходитися у цій місцевості задля відновлення первозданної історичної концепції архітектурного довкілля та створення унікального, приналежного до цієї території, предметно–просторового середовища, що також призведе до підвищення якості інфраструктури та інформативності простору міста. Результати дослідження відкривають перспективи подальшої наукової та практичної розробки концепції організації дизайн-об’єктів інформаціно–комунікативних середовищ міст України та формування «дизайн-коду» міста Харкова. В диссертации представлены результаты исследования проектно-художественной организации дизайн-объектов информационно-коммуникативных сред. Автором выделены практические мировые приемы задействования дизайн-объектов в пространства городов. Виды информационно-коммуникативных сред и поводы к их реорганизации. Выявлены функциональные приоритеты дизайн-объектов в городском пространстве относительно их «духовных» и «телесных» свойств. Исследован ряд реорганизованных и исторических локаций города для выявления положительных и отрицательных информационно–коммуникативных качеств. Анализируется современное состояние теоретического наследия в развитии собственного «дизайн-кода» города. В ходе исследования предлагается ряд инновационных принципов и приемов, которые помогут реорганизовать современное положение информационно–коммуникативного пространства с учетом функциональности каждой отдельной локации и собственной эстетической идентификации. Выделяется комплекс интерактивного и новейшего оборудования, которое должно находиться в этой местности для восстановления первозданной исторической концепции архитектурного пространства и создания уникальной, относящейся к этой территории, предметно–пространственной среды, что также приведет к повышению качества инфраструктуры и информативности территорий города. Результаты исследования открывают перспективы дальнейшей научной и практической разработки концепции организации дизайн-объектов информационно-коммуникативных сред городов Украины и формирования «дизайн-кода» города Харькова. В диссертации представлены результаты исследования проектно-художественной организации дизайн-объектов информационно-коммуникативных сред. Автором выделены практические мировые приемы задействования дизайн-объектов в пространства городов. Виды информационно-коммуникативных сред и поводы к их реорганизации. Выявлены функциональные приоритеты дизайн-объектов в городском пространстве относительно их «духовных» и «телесных» свойств. Исследован ряд реорганизованных и исторических локаций города для выявления положительных и отрицательных информационно–коммуникативных качеств. Анализируется современное состояние теоретического наследия в развитии собственного «дизайн-кода» города. В ходе исследования предлагается ряд инновационных принципов и приемов, которые помогут реорганизовать современное положение информационно–коммуникативного пространства с учетом функциональности каждой отдельной локации и собственной эстетической идентификации. Выделяется комплекс интерактивного и новейшего оборудования, которое должно находиться в этой местности для восстановления первозданной исторической концепции архитектурного пространства и создания уникальной, относящейся к этой территории, предметно–пространственной среды, что также приведет к повышению качества инфраструктуры и информативности территорий города. Результаты исследования открывают перспективы дальнейшей научной и практической разработки концепции организации дизайн-объектов информационно-коммуникативных сред городов Украины и формирования «дизайн-кода» города Харькова. The thesis presents the results of the study of the system of factors forming the informational and communicative environment of the city in terms of the design objects structural principles in the urban environment. Counterparts of the city informational and communicative environment are identifying as a complex phenomenon of the design-object action in the urban environment. The content of concepts 'design object', 'informational and communicative environment', 'communicative design is analyzed. In the first section ('Historiography of the issue and methods of research') literary sources are analyzed and systematized, the classification of objects of research is given, the modern conceptual apparatus is considered in the research area of design, the methodological approach is determined. The problems of information design objects organization within the framework of historical development of communicative design are investigating; active use of coloring, lighting, and interactive technologies in the organization of communicative environment; formation of architectural-landscape environment aesthetics and filling it with 19 design objects; sign-semantic, socio-cultural, psychological and economic orientation– provided a comprehensive coverage of the artistic-and-figurative and form-shaping features of contemporary communicative design objects. The second section ('Communicative design as a means of shaping the urban informational environment') the methods of building the informational and communicative environment in the world are highlighted and the functional qualities and priorities of the design object as one of its components are considered. The typology of all design objects of the informational and communicative environment with respect to functional priorities in the city environment was proposing: advertisement-informational objects, navigational objects, communicative objects. The components of the urban informational-communicative environment were identified – 'design', 'architecture', 'information', 'man' – and a number of attending qualities ('spiritual' and 'bodily') of the priority influence of the informational design objects on these components: 'design' – means and artistic figurality; 'architecture' – stylistics and structure; 'man" – aesthetics and ergonomics; 'information' – semantics and format. In the third section ('Features of the organization of urban informational and communicative environment design objects of the city of Kharkiv') the current state of informational and communicative environments of the city of Kharkiv is analyzing while identifying drawbacks and advantages. The problems of the design objects organization in the urban environment are outlining. It was revealed that the main reason for the creation of 'visual noise' and violations of environmental communicative in the city is the lack of clearly established rules for the priority placement of informational-and-navigation and advertising design objects in the urban environment. As a result, in the most populated city areas, with a high percentage of visits, there is a shortage in necessary number of city terminals, ATMs, access points to the WI-FI network, and in some areas, even traffic lights. In addition, advertising entrepreneurs place design objects chaotically, pursuing one and only goal: creating more significant and noticeable 'spot' in urban environment. In the fourth section ('Strategy for a modern city design code creation'), the of informational and communicative design objects organizational principles are outlined on the basis of the above-mentioned methods, as well as the conceptual methods for its further development in order to form their own urban 'design code'. The recommendations for the practical implementation of the discovered theoretical achievements of the anesthetization of the city informational and communicative environment in Kharkiv have been forming. It is revealing that transformability, mobility, interactivity of environmental design objects contribute to the creation of a more comfortable humanized informational and communicative environment for human activities and habitation. Ideas of adaptability help creation of expressive artistic and plastic design solutions, which are still relevant and satisfy the needs of ecology, aesthetics and society. Implementation of the adaptation principles of informational and communicative environmental objects opens up great prospects for use scientific and technological developments that generate new ideas, in the design. The thesis outlines the appropriate prerequisites for the reorganization of the urban object-spatial environment on the example of city Kharkiv, in order to improve the informational and communicative qualities of the territory: low expedient informatization of the city's environment; non-subordination of information dimensional-plastic forms; lack of aesthetic harmony of the urban environment; loss of connection with the surrounding architectural and landscape environment; lack of perfection or imperfection of interactive objects; consciousness of national cultural authenticity; threatening psycho-emotional state of man in the man-made city environment. The specificity of the orientation of informational and communicative design objects in the city of Kharkiv environment is characterizing. It is determined that from the point of view of artistic-figurative expediency of the objective world, not only external - 'physical', but also 'internal' - 'spiritual' harmony is of importance. For the first time, the methods and principles of organizing the design objects of the modern urban informational and communicative environment have been developed and classified. It has been establishing that, thanks to the world design practice, a number of artistic-figurative and technical devices that are actively used, are being implemented.
Особенности организации дизайн-объектов информационно-коммуникативной среды современного города (на примере г. Харьков)
Features of informational and communicative environment of the city design objects organization (using the city of Kharkiv as an example)
Keywords: інформація; комунікація; дизайн-об’єкти; «дизайн-код»; принципи; прийоми; інтерактивність; інновація; информация; коммуникация; дизайн-объекты; «дизайн-код»; принципы; приемы; интерактивность; инновация; design object; informational and communicative design environment; communicative design; 72.007